Cytotoxicity, genotoxicity, and impact on populations of the mangrove sentinel species, Ucides cordatus (Linnaeus, 1763) (Brachyura, Ocypodidae) after an environmental disaster at Cubatao, Sao Paulo, Brazil - Pinheiro, Marcelo Antonio Amaro [UNESP]; Souza, Fernanda Vargas Barbi de [UNESP]; Boos, Harry; Duarte, Luis Felipe de Almeida (Soc Brasileira Carcinologia, 2022)
In 2015, a serious environmental disaster occurred at ULTRACARGO -Aratu S/A Terminal (Cubatao, SP) causing a long-lasting, large-scale, fire that resulted in the release of various chemical pollutants, including those used to contain the fire. These pollutants affected adjacent regions and the innermost area of the Santos-Sao Vicente Estuarine System, requiring the assessment of environmental quality in two mangrove areas post-disaster (2016). This assessment considered biomarkers for the species including population density, structure, and cytogenotoxicity. The population structure and cytotoxicity of Ucides cordatus (Linnaeus, 1763) only changed slightly from pre-disaster (2013) to post-disaster (2016), as a consequence of the greater resilience and biological flexibility of this crab to environmental stress caused by pollutants. We recommend continuous monitoring be conducted using this species endemic to the mangroves of the study site, as this will make it possible to assess the magnitude of the chronic environmental impacts of the accident. In addition, it could guide environmental agencies in damage mitigation or in the quantification of possible future impacts.
Keywords: Biomarkers; crab; environmental disaster; estuary; Ucides cordatus